Nutrition and Cardiovascular Health - Tappia, Paramjit S.; Blewett, Heather (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There is unequivocal experimental, epidemiological, and clinical evidence demonstrating a correlation between diet and increased risk of cardiovascular disease (CVD). While nutritionally-poor diets can have a significant negative impact on cardiovascular health, dietary interventions with specific nutrients and/or functional foods are considered cost-effective and efficient components of prevention strategies. It has been estimated that nutritional factors may be responsible for approximately 40% of all CVD. Indeed, in one of the seminal studies conducted on modifiable risk factors and heart health (the INTERHEART study), >90% of all myocardial infarctions were attributed to preventable environmental factors with nutrition identified as one of the important determinants of CVD. There is an increasing public interest in and scientific investigation into establishing dietary approaches that can be undertaken for the prevention and treatment of CVD. This Special Issue provides an insight into the influential role of nutrition and dietary habits on cardiovascular health and disease, as well as their mechanisms of therapeutic and preventive action.